ANALISIS PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL PADA FORUM OSIS BANDUNG BARAT (FOBB) - dini, dini; fizi (JEBIM Prima, 2024)
The West Bandung OSIS Forum (FOBB) is a special forum or organization for West Bandung Regency OSIS administrators. FOBB can be a strategic and important forum in efforts to hone leadership, character, competence and literacy among West Bandung Regency students. The successful implementation of this FOBB is certainly not far from the leadership style of the FOBB currently in office. Therefore, the aim of this research is to identify and analyze the transformational leadership that occurs at the West Bandung OSIS Forum. The analysis carried out is based on the characteristics of transformational leaders which consist of ideal influence or charisma, Inspirational Motivation, Intellectual Stimulation and individual attention. The type of research carried out was qualitative research with the determination of informants using purposive sampling and data collection techniques using observation and interviews. The research results show that the leader of the West Bandung OSIS Forum has implemented transformational leadership, and meets every characteristic of a transformational leader, however the transformational leadership that has been implemented still needs to be maximized so that the forum and members can continue to develop. Keywords: Character, Leadership, Transformational